France : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper focuses on various aspects of corporate debt in France. The increase in debt has financed real investments, as well as acquisition of financial assets and extension of intercompany loans. The increase in debt (and its level) appears less worrisome when debt is consolidated among nonfinancial corporations. Despite the increase in the stock of debt, debt service has increased moderately. A cross-country regression analysis reveals that French publicly listed firms are on average not more indebted and have not increased their debt more than peers in other countries, after controlling for firm and sector characteristics as well as common time effects. However, the increase in debt is concentrated among large firms with sizeable leverage in a few industries, raising questions about these firms' ability to service this debt when interest rates rise. Stress test scenarios of a large and sudden increase in interest rates suggest that corporate debt at risk could be significant at a macroeconomic level, but that cash buffers would mitigate the impact of the shock on debt service.